PREVALENCE OF CYTOMEGALOVIRUS IN CHILDREN WHO RECEIVE BONE MARROW TRANSPLANTATION BY MEANS OF REAL-TIME POLYMERASE CHAIN REACTION - López-Montanero Edith Elizabeth; Moscoso-Solórzano Grace Támara; Alvarado-Villa Geovanny; Maldonado-Guerrero Bella Irma; Frías-Toral Evelyn Paola; Jiménez-Jiménez Fanny Maribel; Iglesias-Arreaga Adriana Lissette (Revista Ciencias Biomédicas, 2015)
Introduction: The citomegalovirus (CMV) is an important virus worldwide. The early and mass-produced detection of the viral load for CMV helps to treat in an early way the infection and to avoid the disease in immunodeficient patients that in several cases could be lethal. Objective: To determine the prevalence of CMV in immunodeficient children who received bone marrow transplantation by means of real-time polymerase chain reaction. Methods: Retrospective, descriptive and cross-sectional study. The viral load was determined in plasma samples recollected since 2009 to 2012 in children who received bone marrow transplantation in the Hospital de la Sociedad de Lucha contra el Cáncer (SOLCA) in Guayaquil, Ecuador. Results: 38 samples were analyzed. The average age was 7.2 years, and 57.9% (n=22) were men and 42.1% (n=16) women, with a male-female relationship 1:4. Of the analyzed samples, five patients presented positive results in the mentioned technique, who were the 80% of the female gender. And the population with the higher number of cases with positive results were Los Ríos, Guayas and Esmeraldas. The patients who were transplanted due to acute lymphoblastic leukemia and lymphoma with leukemization to acute lymphoblastic leukemia had positive results for active infection by CMV, 80% and 20%, respectively. Conclusion: The prevalence of CMV in children who received bone marrow transplantation by means of real-time polymerase chain reaction was of 13%, higher in the female gender. Rev.cienc.biomed. 2015;6(1):53-59 KEYWORDS Cytomegalovirus; Cytomegalovirus Infections; Transplant Recipients; Polymerase Chain Reaction.